2004
DOI: 10.1097/01.tp.0000128343.88355.14
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cytomegalovirus Disease with Valganciclovir in Renal Transplant Recipients: A Single Center Experience

Abstract: Recent data suggest valganciclovir (VGC) to be as effective as ganciclovir for cytomegalovirus (CMV) prophylaxis. The objective of this study was to analyze the effect of oral valganciclovir in renal transplant patients with symptomatic CMV infection. Twenty-one patients with symptomatic CMV infection received VGC in doses adjusted to renal function until resolution of CMV antigenemia. The patients were followed for a mean of 5.5 months. During therapy, CMV antigenemia dropped in all patients from pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…Our data showed that the proportion of CMV-positive donors and CMV-negative recipients was greater for episodes that experienced relapse (14.3%) than for those that experienced success (9.6%), although the difference was not statistically significant. Again, a previous study of valganciclovir as preemptive therapy reported a recurrence rate similar to ours [10]. In that study, CMV disease occurred mainly in the late posttransplantation period, and many cases were likely to have been late reactivations of infection, which are associated with a lower risk of recurrence [10].…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Our data showed that the proportion of CMV-positive donors and CMV-negative recipients was greater for episodes that experienced relapse (14.3%) than for those that experienced success (9.6%), although the difference was not statistically significant. Again, a previous study of valganciclovir as preemptive therapy reported a recurrence rate similar to ours [10]. In that study, CMV disease occurred mainly in the late posttransplantation period, and many cases were likely to have been late reactivations of infection, which are associated with a lower risk of recurrence [10].…”
Section: Discussionmentioning
confidence: 48%
“…The reported data in the literature regarding such patients are very sparse and quite limited but point in the direction of our findings [10][11][12][13][14][15][16][17]. In various populations, involving a small number of patients and no comparison groups, including renal [10], cardiac [11,12], lung [12,15], and liver [17] transplant recipients, valganciclovir seemed to be effective and safe as either preemptive therapy or treatment for viral syndrome. It has been also reported that valganciclovir reduces the CMV DNA level in a manner similar to that of intravenous ganciclovir when given as part of a preemptive strategy [13,16].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…TGF-b1 g.869T > C polymorphism was observed to provide risk towards DN in Mexican (Valladares-salgado et al, 2010) and Chinese populations (Wong et al, 2003) and towards ESRD in a North Indian population (Mittal and Manchanda, 2007). Contrarily, reports on German and Spanish populations concluded that 869T allele rather than C allele was associated with ESRD susceptibility (Babel et al, 2006;Coll et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Si bien no existen estudios clínicos aleatorios publicados, en pacientes con trasplante renal y enfermedad por CMV el tratamiento con valganciclovir hasta la resolución de la antigenemia fue satisfactorio y no se siguió de recidiva 101 . Una dosis de 900 mg es equiparable (área bajo la curva) a una dosis de 5 mg/kg de ganciclovir intravenoso.…”
Section: Tratamiento De La Enfermedad Por CMVunclassified